Numerical modeling and validating waves generated by typhoons in the East Vietnam Sea using satellite data - Pham Tien, Dat; Nguyen Minh , Huan; Nguyen Phuong, Anh (Vietnam Journal of Marine Science and Technology, 2021)
Calculating waves generated by typhoons is one of the most important tasks for wave forecasting at a stormy region like the East Vietnam Sea. It is, however, difficult to access the accuracy of calculated wave heights due to the lack of observed data. An approach of combining numerical models and satellite data has been widely used. In this study, we used the WAVEWATCH III model to stimulate wave fields caused by three strong typhoons: Damrey (2005), Ketsana (2009) and Haiyan (2013), then compared significant wave heights with the merged satellite observations. The results show that the BIAS values are small and negative, indicating that the wave heights from the model are lower than those from satellites in all cases. In contrast, the RMSE values of the three cases are considerably different but are still below 1 m. Finally, the average correlation coefficient is highest in typhoon Damrey (r = 0.94) whereas in typhoon Ketsana and Haiyan, r = 0.84 and r = 0.87, respectively. In conclusion, the study suggests that the WAVEWATCH III model has good performance for typhoon wave calculations and can be useful for wave forecasting in the East Vietnam Sea.